Adiponectin and Total Antioxidant Capacity and Their Association with Insulin Resistance Among Women with Polycystic Ovarian Syndrome - Fatimah Fathi (University of Mosul, 2024)
Background and objectives: Polycystic ovary syndrome (PCOS) is a hormonal disorder characterized by an imbalance in women's reproductive hormones within the endocrine system. PCOS is related to metabolic and endocrine disorders, including insulin resistance, glucose intolerance, obesity, diabetes mellitus, acne, and hirsutism. Obesity is common in PCOS-affected women, and it leads to abnormalities in adipocyte function and adipokine levels, including adiponectin. Adiponectin is a homeostatic regulatory agent for glucose, lipids, and insulin by its anti-inflammatory, antioxidant, and anti-fibrotic actions. It is hypothesized that the metabolic and endocrine disturbances observed in PCOS women may be related to altered adiponectin levels. Methods: Thirty-two women with PCOS under 35 years-old were enrolled in the current study, and 32 healthy women were matched for age with the previous group to evaluate adiponectin levels, total antioxidant capacity, glucose, and insulin resistance. Results: Compared with the control group, women with PCOS had significantly reduced levels of total antioxidant capacity, and adiponectin (P<0.05), with a concomitant significant increase in glucose and insulin levels and insulin resistance (P<0.0001). Interestingly, no statistically significant correlations were observed between the parameters. Conclusions: Accordingly, we concluded that lower adiponectin levels and total antioxidant capacity together with higher glucose and insulin levels and insulin resistance may offer predictive risk factors for PCOS in women who are obese with fewer PCOS symptoms.